Pelaksanaan Diskresi Pada Penanganan Pandemi Covid 19 DiIndonesia - Iskatrinah (Wijayakusuma Law Review, 2021)
The purpose of this paper is to analyze the harmonization of the principle of discretion in government over thepolicies of the central government with local governments in handling the Covid 19 pandemic in Indonesia. Theresearch method used in this research is to use normative legal research methods, with the result that the spreadof the Corona Virus in Indonesia has made the government, local governments, and the Indonesian peoplecontinue to be alert and alert. Vigilance and preparedness are important so that prevention and control of thecorona virus pandemic in Indonesia can be done as well as possible. The form of handling the Covid 19 pandemic,both the central and local governments, both provincial and district / city, have implemented existing legalinstruments and issued approaches both social approaches and legal instruments issued by authorizedgovernment officials through freedom of action or discretion as an effort to harmonize central governmentpolicies with local governments.